Achieving Graduate Competency Standards: Impact of The Excellence Program - Agus Zaenul Fitri (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2018)
The purpose of this paper is to reveal the results of the efforts and strategies to improve the quality of graduates in achieving competency standards in FTIK (Fakultas Keguruan dan Ilmu Pendidikan/Faculty of Education and Teacher Training) at The State Islamic University of Malang, Indonesia. The existing challenge today, namely the ASEAN Economic Community (AEC) in which the human resources with special requirements, is to be able to compete and work at any positions wherever they want. An Islamic college, particularly the FTIK where the prospective educators are “born”, should be able to produce graduates who have both national and international qualifications. As a result, it demands the necessary management and strategies to achieve SKL (Standar Kompetensi Lulusan/ Graduate Competency Standard). This study uses qualitative approach with field research type. Strategies to guarantee the quality of graduates done through tight assessment, provision of extra programs that can improve the students' academic quality, continuous assessment, and the students’ scientific work must be written in either English or Arabic. Excellence program has a positive impact either on students who want to continue to pursue higher education or students who choose to work. The graduates of excellence programs are proven to have tough mentality as well as high work ethics.